REPRESENTASI MAKNA KEHIDUPAN DAN EMOSI DALAM LIRIK LAGU ALBUM MEMBANGUN DAN MENGHANCURKAN KARYA FEAST: KAJIAN PSIKOLOGI SASTRA - Yunita Sari; Elmustian; Mangatur Sinaga (JURNAL SKRIPTA, 2026)
This study explores the relationship between songs, emotions and the construction of the meaning of life built through David Krech's psychological classification theory. Songs function as a medium that is not only entertainment but also an expression of feelings that can be adapted from the actual situation and also the experience of individuals in a certain space and time, the main purpose of this study is to identify the types of emotions that exist in the lyrics of the album building and destroying feast works. In addition, the study also aims to analyze and describe in detail how the meaning of life can be a factor in influencing the emotions of individuals, through David Krech's classification of emotions with a descriptive qualitative research method approach, the results of the data findings will be analyzed according to the technique and also through valid data sources to test its validity. In addition, this study also explains that song lyrics can be studied through the study of literary psychology which indirectly becomes a reference and also education for readers that literature lives in the daily lives of individuals and is unconsciously able to provide the best contribution to the readers of this study, this study is expected to be able to contribute to further research on the study of literary psychology